2
$\begingroup$

There's a mapping $f:X\rightarrow Y$.

1.for all $A,B\subset X$, $f(A\cap B)=f(A)\cap f(B)$, prove $f$ is injective.

2.for all $A\subset X$, $f(A^{c})=[f(A)]^{c}$, prove $f$ is bijective.

$\endgroup$
  • $\begingroup$ Try to show us what you have tried yourself, and where you got stuck. This way we can help you more effectively! You will also learn a lot more this way. $\endgroup$ – sxd Sep 9 '12 at 15:05
4
$\begingroup$

For 1 you want to show that $f(x) = f(y)$ implies $x = y$. So let $f(x) = f(y)$. Then $f(\{x\}) = f(\{y\})$ and hence $f(\{x\}) \cap f(\{y\}) = f(\{x\}) = f(\{y\}) = f(\{x\} \cap \{y\})$. Hence $x=y$.

$\endgroup$
  • $\begingroup$ Now try to do 2 in a similar way. $\endgroup$ – Rudy the Reindeer Sep 9 '12 at 15:06
0
$\begingroup$

(1) Suppose $f$ is not injective. That is, there exists $a \neq b$ such that $f(a) = f(b)$. Consider the sets $\{a\}$ and $\{b\}$. Then $f(\{a\} \cap \{b\}) = f(\emptyset) = \emptyset \neq f(\{a\}) \cap f(\{b\})$.

(2) Suppose $f$ is not injective. Then there exists an $x$ such that $f^{-1}(x)$ contains more than a single element. Let $a \in f^{-1}(x)$. Let $A = f^{-1}(x) - \{a\}$. Then $x \in f(A^c)$ but $x \notin f(A)^c$. So $f(A^c) \neq f(A)^c$.

Suppose that $f$ is not surjective. Then there exists a $y \in Y$ such that $y \notin f(X)$. Let $A = X$. Then $f(A^c) = f(\emptyset) = \emptyset$. However $y \in f(A)^c$. Hence $f(A^c) \neq f(A)^c$.

Thus, it has been shown that $f$ is injective and surjective.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.